The development of emotional overeating: a longitudinal twin study from toddlerhood to early adolescence - Vaishnavi K. Madhavan; Zeynep Nas; Jacqueline Blissett; Clare Llewellyn; Moritz Herle (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Previous research has estimated the genetic and environmental contribution to individual differences in emotional overeating in toddlerhood and early childhood. However, little is known how this behaviour tracks into adolescence. Here, we aimed to replicated previous work and examine the aetiology of stability and change in emotional overeating across time. Methods Data were from the UK Gemini Twin Study, which includes 2402 twin pairs born in 2007. Parents reported on children’s emotional overeating at 16 months (n = 3784), 5 years (n = 2064), and 12 years (n = 964), using the Emotional Overeating Scale of the Child Eating Behaviour Questionnaire (CEBQ) at 5 and 12 years, and the CEBQ-T (toddler version) at 16 months. A Cholesky Decomposition twin model was used to quantify the additive genetic, shared, and nonshared environmental influences on emotional overeating at each time point, partitioned into aetiological effects unique to each age and those carried across time. Results Additive genetic effects were minimal at 16 months and 5 years (9% and 7% respectively) but increased to 34% by 12 years. Shared environmental effects explained the majority of variance in emotional overeating at all three time points, but significantly less at 12 years (41%) than earlier (> 81%). The longitudinal phenotypic associations (r = 0.23–0.43) were explained by the shared environment. Conclusion The shared environment plays a major role in the development of emotional overeating in early life. Most aetiological influences on emotional overeating were unique to each age, indicating the need for family-based interventions targeted to each developmental stage.